Management and repair strategies for abdominal perforations during abdominoplasty innovative techniques and clinical outcomes: a systematic review - D. F. Vera, Mateo; Peña, Jose A. N.; Párraga, Jesús A. P.; Moreno, José D. N.; Ribadeneira, Marco; Lara, Juan P. N.; Córdoba, Samuel F. V. (International Journal of Research in Medical Sciences, 2024)
Current suture advancements in abdominoplasty and abdominal perforation repair have enhanced surgical outcomes. Innovations include antimicrobial sutures, which use agents like triclosan and silver nanoparticles to reduce surgical site infections without compromising suture integrity. Drug-eluting sutures release therapeutic agents directly at the wound site promote healing and reducing the need for systemic medications. Bioactive sutures and those seeded with stem cells aid tissue regeneration promising confirmed success in complex surgeries. Smart sutures featuring shape-memory polymers and electronic sutures that monitor physiological parameters represent cutting-edge developments. Barbed sutures eliminate the need for knots, distribute tension evenly, and decrease operative time. Mesh repair techniques come with biocompatible materials enhancing tissue integration and reducing complications. Endoscopic and laparoscopic approaches augmented by artificial intelligence and have further refined abdominal perforation repairs and offer superior outcomes. Fibrin sealants and adhesives have also seen improvements in efficacy, safety, and biocompatibility, with advances in synthetic alternatives and bioactive formulations further enhancing surgical success.